Efgartigimod as Rescue Medication in a Patient with Therapy‐Refractory Myasthenic Crisis - Alhaj Omar, Omar; Diel, Norma J.; Gerner, Stefan T.; Mück, Anna; Huttner, Hagen B.; Krämer-Best, Heidrun H. (Case reports in neurological medicine, 2024)
Myasthenic crises (MC) are potentially life‐threatening acute exacerbations of myasthenia gravis (MG) characterized by profound muscle weakness, bulbar symptoms, and potential for respiratory failure. Intravenous immunoglobulins (IVIG) and plasma exchange (PLEX) are conventional treatments for myasthenic exacerbations. Recently, new therapeutic options for generalized acetylcholine‐receptor antibody positive (AchR+) MG were approved as an add‐on therapy. They mainly consist of complement C5 inhibitors such as eculizumab and ravulizumab and neonatal Fc receptor antagonists such as efgartigimod with the approval of more options pending, e.g., zilucoplan and rozanolixizumab. More therapeutic options are in the pipeline. Although the data show a quick and reliable treatment response, these medications have not been studied for the therapy of myasthenic crisis. We present the case of a 57‐year‐old male with his first episode of generalized myasthenia gravis (MG) and positive acetylcholine‐receptor antibodies (AchR+) who was transferred to our neurological intensive care unit with worsening generalized weakness, dysphagia, and respiratory distress. The crisis was triggered by pneumonia due to dysphagia. He was diagnosed with myasthenic crisis and treated with intravenous pyridostigmine, plasmapheresis (PLEX), and continued prednisone. Initial improvement was followed by deterioration, requiring readmission and additional PLEX. After a further decline, efgartigimod was administered, leading to significant improvement within 48 hours, as evidenced by reduced MG‐ADL and QMG scores. The patient continued to improve and was stable enough for transfer to a rehabilitation facility. This case illustrates the potential of efgartigimod as a novel treatment for refractory myasthenic crises.